PELATIHAN PEMANFAATAN WHATSAPP BUSINESS DALAM PELAYANAN KEPADA MASYARAKAT DESA DI KECAMATAN KERTAJATI - Rosshad, Anwar; Dewi Primasari, Vinda Verina Kartika; Suryapuspita, Merintha; Rahmah, Mutia (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2024)
The realization of public services that are fast, easy, and accessible from anywhere is a concern for the village government as the institution closest to the community. The aim of this community service is to provide skills for service providers in villages through training in the use of WhatsApp Business in Kertajati District. To achieve this goal, this service activity is carried out using the introduction and training method through the pre-implementation, implementation, and post-implementation stages. This activity was attended by 42 people who were representatives from 14 villages in Kertajati District including village officials, BPD representatives, neighborhood chairman and representatives of Kertajati District employees. The results of community service show that there has been an increase in the participants' understanding and skills through training on the use of WhatsApp Business in services to village communities in Kertajati District. This can be seen from measuring the average pre-test and post-test scores of the participants through surveys. In the future, there is a need to increase the capacity of village officials in a planned and sustainable manner in realizing the expected public services. Apart from also providing village facilities to optimize the implementation of services in the village.Perwujudan pelayanan publik yang cepat, mudah, dan dapat diakses dari manapun menjadi perhatian bagi pemerintah desa sebagai institusi yang paling dekat dengan masyarakat. Tujuan pengabdian masyarakat ini adalah untuk memberikan keterampilan bagi penyelenggara pelayanan di desa melalui pelatihan pemanfaatan WhatsApp Business di Kecamatan Kertajati. Untuk mencapai tujuan tersebut, kegiatan pengabdian ini dilakukan dengan metode pengenalan dan pelatihan melalui tahap pra pelaksanaan, pelaksanaan, dan pasca pelaksanaan. Kegiatan ini diikuti sebanyak 42 orang yang merupakan perwakilan dari 14 desa di Kecamatan Kertajati meliputi aparat desa, perwakilan BPD, kepala dusun dan perwakilan pegawai Kecamatan Kertajati. Hasil pengabdian masyarakat menunjukkan bahwa terjadi peningkatan pemahaman dan keterampilan para peserta melalui pelatihan pemanfaatan WhatsApp Business dalam pelayanan kepada masyarakat desa di Kecamatan Kertajati. Hal ini terlihat dari pengukuran nilai rata-rata pre-test dan post-test para peserta melalui survei. Ke depan, perlu adanya peningkatan kapasitas bagi aparatur desa yang terencana dan berkelanjutan dalam mewujudkan pelayanan publik yang diharapkan. Selain juga penyediaan sarana dan fasilitas desa untuk mengoptimalkan penyelenggaraan pelayanan di desa.